Unravelling the peroxisome-dependent MAVS signalling pathway - Matos, Carolina Branquinho de (2021)
The cellular antiviral immune response is triggered upon recognition of specific viral components by a set of host proteins such as the retinoic acid inducible gene-I (RIG-I). Upon viral stimulation, RIG-I undergoes a conformational change and interacts with the mitochondrial antiviral signalling adaptor (MAVS) at mitochondria and peroxisomes, initiating a signalling cascade that culminates with the production of antiviral effectors, preventing important steps in viral propagation. Peroxisomes and mitochondria have been shown to act in concert as important signalling platforms within this mechanism: while the peroxisomal pathway induces the rapid expression of defense factors providing short-term protection, the mitochondrial pathway activates a signalling cascade with delayed kinetics that amplifies and stabilizes the antiviral response. This suggests the existence of two distinct signalling cascades originating from both organelles. The mitochondrial signalling pathway has been extensively studied and most of its components have already been identified. With this study, we aimed to unveil the components of the peroxisome-dependent pathway, by investigating the possible involvement of proteins that also belong to the mitochondrial pathway. To that end, we used cells that contain MAVS solely at peroxisomes and overexpressed viral proteins that have been shown to inhibit specific steps of the mitochondrial MAVS pathway: UL36 from herpes simplex virus (shown to cleave the polyubiquitin chains of TRAF3 inhibiting the recruitment of TBK1) or NP from lymphocytic choriomeningitis virus (associates with IKKe blocking its ability to phosphorylate IRF3). These cells were virally-stimulated and antiviral signalling was analysed by RT-qPCR and immunoblot. Our results revealed that UL36 and NP also inhibited the antiviral signalling in these cells, indicating the presence of TRAF3 and IKKe as downstream molecules of MAVS on the peroxisomaldependent antiviral signalling pathway